2022
DOI: 10.1371/journal.pone.0265151
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular correlates of sleep apnea phenotypes: Results from the Hispanic Community Health Study/Study of Latinos (HCHS/SOL)

Abstract: Background Identifying Obstructive Sleep Apnea (OSA) phenotypes among middle-aged and older Hispanics/Latinos can facilitate personalized care, better inform treatment decisions, and could lead to improved clinical outcomes. Methods We focused on middle-aged and older adults (ages ≥45–74 years at baseline) with an apnea-hypopnea index (AHI) ≥5 from the HCHS/SOL (2008–2011) (unweighted n = 3,545). We used latent class analyses (LCA) to identify empirical and clinically meaningful OSA phenotypes. Sleep variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…Results were also corroborated by stronger effects of greater PAP utilization against MI among those with evidence of hypersomnia. These results support the well-established epidemiological relationship between excessive daytime sleepiness and increased CV risk among those with OSA 14,15,64,65 . It is important to note that granular measures of excessive daytime sleepiness might provide a more robust phenotype when compared to claims for hypersomnia.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Results were also corroborated by stronger effects of greater PAP utilization against MI among those with evidence of hypersomnia. These results support the well-established epidemiological relationship between excessive daytime sleepiness and increased CV risk among those with OSA 14,15,64,65 . It is important to note that granular measures of excessive daytime sleepiness might provide a more robust phenotype when compared to claims for hypersomnia.…”
Section: Discussionsupporting
confidence: 88%
“…Many patients present with excessive daytime sleepiness, which was an important exclusion criterion in these trials, due to the ethical reason of randomising patients that are excessively sleepy into control arms 29 . However, we 14,62 and others 15,63 have demonstrated this subgroup is at increased risk for incident CV diseases. These observations suggest that alternative approaches using causal inference in well-designed observational studies could provide more generalisable evidence towards the role of PAP therapy on CV outcomes risk.…”
Section: Discussionmentioning
confidence: 58%
“…[16][17][18] Although the main limitation is the lack of external validation, other cluster analyses on obstructive sleep apnoea have been published. 19 In a 2022 study, subpopulations of patients with obstructive sleep apnoea were defined with latent class analysis in a cohort of Hispanic patients based in the community, and an association between symptom clusters of obstructive sleep apnoea and cardiovascular disease was identified 20 ; the insomnia obstructive sleep apnoea phenotype (apnoea-hypopnoea index mean 10.5 events/h (standard deviation 5.2)) was associated with an increased incidence of cardiovascular and cerebrovascular disease (heart failure, hypertension, and diabetes) compared with those with no obstructive sleep apnoea. Other studies have shown a potential increased risk of cardiovascular and cerebrovascular disease in relation to symptoms of insomnia; for example, in the study by Labarca and colleagues, the disturbed sleep cluster had an increased but non-significant hazard ratio for cardiovascular events (2.87, P=0.11).…”
Section: Symptom Clustersmentioning
confidence: 99%
“…The risk of stroke is directly related to OSA severity [23]; however, a definite phenotype of OSA, such as biomarkers predictive of cerebrovascular injury, is still missing. Recent evidence suggests that incidence of stroke is significantly higher in patients with OSA showing excessive daytime sleepiness (EDS) [24,25]. Conversely, another recent research did not show any association between OSA symptoms and risk of cardiovascular diseases [26], but identified hypoxic burden, defined as the area under the desaturation curve associated with respiratory events, as a promising marker of cardiovascular risk in OSA population [26,27].…”
Section: Sleep Apnea As Risk Factor For Strokementioning
confidence: 99%